Changing Dietary Behavior in Elderly with Hypertension through Hypertension Random Card Game: Perubahan Perilaku Diet pada Lansia Penderita Hipertensi melalui Permainan Kartu Acak Hipertensi - Susila, Wahyu Dini Candra (Jurnal Soeropati, 2022)
The main factor in the problems of hypertensive patients is lack of dietary compliance. Consumption of high sodium and high fat causes uncontrolled hypertension, leading to complications such as stroke. Efforts to treat hypertension with a dietary approach are the Dietary Approach to Stop Hypertension (DASH). DASH, which has been modified in the form of a hypertension random card game, is a method of improving the dietary patterns of the elderly. The implementation of community service to change dietary behavior in elderly people with hypertension uses a case series method where the number of respondents is 17 elderly people. After health education and playing the Hypertension Random Card Game, the elderly experienced an increase in dietary behavior changes, namely 14 elderly (82%) in the positive category or already on a hypertension diet and 2 elderly (18%) in the negative category or not yet on a hypertension diet. Health education with educational games is more fun than health education with conventional lecture and discussion methods. After the intervention, the hypertension diet behavior of the elderly in all aspects including cognitive aspects, affective aspects, and psychomotor aspects has increased. Recommendations that can be given are to conduct periodic evaluations on hypertension diet behavior through hypertension random card games so that a more detailed analysis picture is obtained.